ASTI benchmarking tool for agricultural R&D in Africa south of the Sahara - Agricultural Science and Technology Indicators (International Food Policy Research Institute, 2015)
The ASTI benchmarking tool enables cross-country comparisons and rankings of key agricultural R&D spending and capacity indicators.